Power vs. force ebook The hidden determinants of human behavior. - Hawkins, David R. (2013)
International Bestseller: Take charge of your personal development—and dive deep into the realms of consciousness—with this groundbreaking road map to understanding human behavior and emotions. The universe holds its breath as we choose, instant by instant, which pathway to follow; for the universe, the very essence of life itself, is highly conscious. Every act, thought, and choice adds to a permanent mosaic; our decisions ripple through the universe of consciousness to affect the lives of all . . . In this life-changing motivational book from a world-renowned psychiatrist, spiritual teacher, and consciousness researcher, you’ll learn how to: · Tap into the genius consciousness that lies within us all · Master your emotions and harness your inner power · Make better decisions and have more peace · Understand the energy dynamics that influence your life An essential guide for anyone seeking to further their spiritual or personal development, Power vs. Force will help you cultivate a more conscious and fulfilling life. Unleash your potential, rise above your limitations, embrace the genius within—and begin your journey toward success and emotional mastery today.